Push-Pull Tests for Site Characterization - Istok, Jonathan David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The push-pull test is a powerful site characterization technique that has been applied to a wide range of problems in contaminant hydrogeology. The theoretical and practical aspects of push-pull testing were initially developed to characterize groundwater aquifers but the method has now been extended to saturated and unsaturated soils and sediments and to surface water bodies. Dr. Istok and his collaborators have been instrumental in the development of these techniques and he is widely recognized as the world$1 (Bs leading expert in push-pull testing, This is the only reference book available on this powerful method.s
Push-pull tests -- Setting up a site -- Evaluation of site -- Improvement of site -- Long-term prognosis -- The shape of things to come -- Analysis.
Keywords: Geography; Hydraulic engineering; Sedimentology; Earth Sciences; Hydrogeology; Geotechnical Engineering & Applied Earth Sciences; Sedimentology; Earth Sciences, general